Love at Your Fingertips. Issue 2 (September 2016) - Walter, Anna‐Maria
Abstract: Since 2006, even the remote mountains of northern Pakistan have been connected to the world through mobile phones. In a society with strict gender segregation, it is giving women new scope for communication. An anthropological study is obtaining new insights through participative observation.